Structural, optical and dielectric properties of Cu1.5Mn1.5O4 spinel nanoparticles. Issue 69 (23rd November 2020) - Hadded, Abir; Massoudi, Jalel; Dhahri, Essebti; Khirouni, Kamel; Costa, B. F. O.
Abstract : In this study, a Cu1.5 Mn1.5 O4 spinel was successfully synthesized by a sol–gel method at 500 °C for 5 h and characterized by different techniques. Abstract : In this study, a Cu1.5 Mn1.5 O4 spinel was successfully synthesized by a sol–gel method at 500 °C for 5 h and characterized by different techniques. X-ray diffraction (XRD), Fourier transformation infrared (FTIR) spectroscopy and Raman spectroscopic analyses confirmed the formation of a spinel cubic structure with the Fd 3̄ m space group. The SEM proves that the grain size of our compound is of the order of 48 nm. Crystallite sizes determined from three estimates are closer to the grain size obtained from the SEM, indicating the single domain nature of the sample. The optical properties of UV-visible spectroscopy for our sample showed that the gap value is equal to 3.82 eV, making our compound a good candidate for optoelectronic applications. For electrical properties, impedance spectroscopy was performed at a frequency range of 40 ≤ frequency ≤ 10 6 Hz. This suggested hoping conduction due to three theoretical models. The latter can be attributed to the correlated barrier hopping (CBH) model in region I, overlapping large polaron tunneling (OLPT) in region II and non-overlapping small polaron tunneling (NSPT) mechanism in region III. One dielectric relaxation is detected from the dielectric impedance and modulus, attributed to grain contributions. This behavior was confirmed by both Nyquist and Argand's plots of dielectric impedance at different measuring temperatures.